On the Necessary Grid Resolution for Verified Calculation of Premixed Laminar Flames (Communications in Computational Physics, 2010)
We consider the grid resolution necessary to resolve combustion in a mixtureof calorically imperfect ideal gases described by detailed kinetics and multicomponenttransport. Using the steady premixed laminar flame as a paradigm, the requiredspatial discretization to capture all detailed physics in the reaction zone is foundvia 1) determination of the finest grid used in a standard software tool which employsadaptive mesh refinement, 2) examination of peak values of intermediate species massfractions in the flame zone as a function of grid size, 3) a formal grid resolution study,and 4) a robust new eigenvalue analysis developed to estimate the finest length scale.Application to laminar premixed flames in hydrogen-air flames reveals that the finestlength scale is on the order of 10−4 cm for combustion at atmospheric pressure. Resolutionat this scale is shown to be necessary to capture detailed species mass fractionprofiles; other features such as steady flame speeds and equilibrium thermochemicalproperties do not have such a stringent length scale requirement.